Improving Thermoregulation for Trauma Patients in the Emergency Department: An Evidence-Based Practice Project. Issue 1 (January 2018) - Saqe-Rockoff, Ada; Schubert, Finn D.; Ciardiello, Amanda; Douglas, Elizabeth
Abstract : Extensive evidence exists on the association between hypothermia and increased morbidity and mortality in trauma patients. Gaps in practice related to temperature assessment have been identified in literature, along with limited personnel knowledge regarding management of patients with accidental hypothermia. An interdisciplinary team identified gaps in practice in our institution regarding temperature assessment and documentation of rewarming and initiated an evidence-based practice project to change practice at our institution. The goals were to decrease time to temperature assessment, increase core temperature assessment, and increase implementation of appropriate rewarming methods. This project used the Iowa Model of Evidence-Based Practice to provide a framework for execution and evaluation. We conducted a literature review to address all aspects of hypothermia, including incidence, associated and contributing factors, prevention, recognition, and treatment. This evidence-based knowledge was then applied to clinical practice through staff education and training, equipment availability, and environmental adjustments. More patients with hypothermia and hyperthermia were identified in 2017, as compared with 2016. There was a significant increase in core temperature assessment from 4% in 2016 to 23% in 2017 ( p < .001). Blanket use in normothermic patients increased in 2017 ( p = .002). This project is an example of how nurses can utilize an evidence-based practice model to translate research into clinical practice. Best practice interventions regarding temperature assessment and rewarming measures for trauma patients can be successfully implemented with negligible cost. Further research should be dedicated to examine barriers to implementation and adherence to evidence-based practice interventions.